Agricultural growth and productivity in africa: recent trends and future outlook - Badiane, Ousmane; Collins, Julia (International Food Policy Research Institute, 2016)
The evidence presented in this chapter indicates how imperative it is that African countries make the necessary efforts to sustain and accelerate the current recovery process. In particular, efforts must be made to foster technological progress more than has been the case in the past. Technological progress is market driven and depends on the development, adoption, and effective use of improved technical inputs and production processes in all segments of value chains.